The Synthesis and Stability Study of Silver Nanoparticles Prepared by Using p-Aminobenzoic Acid as Reducing and Stabilizing Agent - Dian Susanthy; Sri Juari Santosa; Eko Sri Kunarti (Universitas Gadjah Mada, 2018)
A study to examine the performance of p-aminobenzoic acid as both reducing agent for silver nitrate to silver nanoparticles (AgNPs) and stabilizing agent for the formed AgNPs has been done. The synthesis of AgNPs was performed by mixing silver nitrate solution as precursor with p-aminobenzoic acid solution and heating it in a boiling water bath. After the solution turned to yellow, the reaction stopped by cooling it in tap water. The formed AgNPs were analyzed by using UV-Vis spectrophotometry to evaluate their SPR absorption in wavelength range of 400–500 nm. The synthesis process was highly depend on the pH, reaction time, and mole ratios of the reactants. The synthesis only occur in pH 11 and at reaction time 30 min, the particle size of the formed AgNPs was 12 ± 7 nm. Longer reaction time increased the reducing performance of p-aminobenzoic acid in AgNPs synthesis but decreased its stabilizing performance. The increase of silver nitrate amount relative to p-aminobenzoic acid in the synthesis increased the reducing and stabilizing performance of p-aminobenzoic acid and the optimum mole ratio between AgNO3 and p-aminobenzoic acid was 5:100 (AgNO3 to p-aminobenzoic acid).